(untitled) (Revista de Ensino em Artes, Moda e Design, 2021)
The Semiotic Theory developed in France by A. J. Greimas and his collaborators, has among its principles to put itself at the service of other social and human sciences. The goal of this paper is to understand how the conceptual architecture of Greimas’ Semiotic theory is used in Design and Fashion researches in Brazil, by conducting a data survey. Our research corpus are the doctoral theses and master’s dissertations defended until 2019 in 25 graduate programs in these areas, filtered according to the use or mention of authors from the French Semiotics field. The main problem was to understand if and how Greimas’ Semiotics presents itself in interdisciplinarity with the researches developed in the Brazilian graduate programs in Design and Fashion. From a total amount of 2,854 thesis and dissertations available in online databases, we found 90 researches that make use of Greimas’ Semiotics. Starting from the opposition between the modes of doing science by separation or by mixing, we identified a typology of the possible relations between disciplines, which can take place either as segregation or comparison operations (separation logics), or even as combination or undifferentiation operations (mixing logics). At large, we found a greater amount of works belonging to the logic of mixture than to the logic of separation, which highlights the very interdisciplinary nature of Design, Fashion and Semiotic areas.